Aluminiumlösungen aus maßgeschneidert wärmebehandelten Halbzeugen - Graser, Matthias; Degner, Julia; Böhm, Wolfgang; Merklein, Marion (Konstruktion, 2017)
LFT Import::2019-07-29 (2271)

Analyse lokaler Kurzzeitwärmebehandlungsmethoden zur Verbesserung des Umformverhaltens und der Bauteileigenschaften von Aluminiumstrangpresshohlprofilen - Graser, Matthias (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2023)
The key issues of the 21st century, such as climate change and electromobility, pose major challenges in the automotive industry. In particular, the continuously increasing vehicle weight, which leads to higher energy consumption, plays a crucial role here. Therefore, one of the most important parameters for improving the ecological balance and increasing the range of modern vehicle concepts is lightweight construction. The increased use of lightweight materials such as aluminum is one way of realizing this concept. However, their low formability compared to ductile steel materials stands in the way of the complete use of aluminum alloys. Therefore, within the scope of this work, a methodology for expanding the shaping limits of extruded aluminum hollow profiles in the bending process is to be developed on the basis of the already known technology for the production of heat-treated aluminum blanks. The basis for this is the development of a basic understanding of the relationships between laser-induced temperature distribution, the resulting locally changed mechanical properties and their influence on the material flow in the bending process. These findings are used to improve the formability and component properties of the hollow profiles and thus further expand their possible areas of applicatio

Application of Tailor Heat Treated Blanks technology in a joining by forming process - Graser, Matthias; Wiesenmayer, Sebastian; Müller, Martin; Merklein, Marion (Journal of Materials Processing Technology, 2019)
The usage of modern materials in the automotive industry for the body in white construction leads to increasing requirements for the manufacturing process. Due to the limited formability of high-strength aluminium alloys and steels, joining by forming of these dissimilar materials is still a big challenge, which requires suitable and innovative manufacturing technologies. In sheet forming processes the Tailor Heat Treated Blank (THTB) technology allows enhancing the formability of high-strength aluminium alloys. Therefore, the applicability of the THTB technology for the shear-clinching technology is investigated in this paper. Up till now, this innovative joining by forming technology is only qualified to join ductile aluminium alloys and high-strength steels, but the combination of high-strength aluminium and high-strength steel has not been realized yet. In this research work, the limits of the shear-clinching process have been extended to successfully join the material combinations of AA7075 on the punch side and HCT780X, as well as press hardened 22MnB5 on the die side by using aluminium specimens with different heat treatment layouts. Further, this paper shows the possibility to adjust the material flow of the shear-clinching process by local and short-term heat treatment.
CRIS-Team WoS Importer:2019-02-21

Efficient Aluminum - Qualifizierung des Einsatzes höchstfester Aluminiumlegierungen im Karosseriebau - Lechner, Michael; Zimmermann, Andrea; Graser, Matthias; Merklein, Marion (Tagungsband zum 1. Green Factory Bavaria Kolloquium 2014 - Engergieeffiziente Produktion, 2014)
LFT Import::2019-08-05 (2044)

Experimental investigation of heat-treated aluminum profiles - Merklein, Marion; Graser, Matthias; Lechner, Michael (Key Engineering Materials, 2015)
Tailor Heat Treated Profiles (THTP) are profiles that exhibit local different mechanical properties optimized for a subsequent forming operation. The property distribution is realized by short term heat treatment before a forming operation. Based on the interaction of soft and hard areas the material flow can be improved and the formability can be enhanced. Prerequisite for a successful application of the technology is a comprehensive material characterization. Therefore, within this paper the influence of short term heat treatment on the mechanical properties of profiles will be presented. In particular, different heating technologies based on heat conduction and laser radiation are compared. Based on the results, a process window will be derived. All investigations were performed using the precipitation hardenable aluminum alloy EN AW 6060.
LFT Import::2019-07-29 (2112)
Keywords: Aluminum profiles; Characterization; Tailored heat treatment

Improvement of the Formability of Aluminum Extrusion Profiles by a Tailored, Local Short-Term Heat Treatment - Merklein, Marion; Lechner, Michael; Graser, Matthias (Proceedings COMA16, 2016)
LFT Import::2019-08-05 (2156)

Influence of a local laser heat treatment on the bending properties of aluminium extrusion profiles - Graser, Matthias; Pflaum, Nico; Merklein, Marion (Procedia CIRP, 2018)
Driven by ecological and economical demands, lightweight design and in this context, the substitution of steel by aluminium has become a major trend in the automotive industry. However, design possibilities are limited by the low formability of aluminium alloys. One approach to overcome these limitations is the usage of tailor heat treated semi-finished products. By a local short-term heat treatment, distinct areas are softened, which can be used to improve the material flow into critical forming zones. Within this work, the influence of local short-term heat treatment on the formability of aluminium extrusion profiles is analysed by experimental bending tests. Aims are the enhancement of maximum reachable bending angles as well as the reduction of cross section deformations. Therefore, different heat treatment layouts are applied by laser irradiation. Finally, the bending results are evaluated and promising heat treatment strategies are derived.
LFT Import::2019-07-29 (2336)
Keywords: Aluminium; Bending; Extrusion profiles; Heat treatment

Influence of a short-term heat treatment on the formability and ageing characteristics of aluminum profiles - Merklein, Marion; Lechner, Michael; Graser, Matthias (Lasers in Manufacturing Conference, 2015)
LFT Import::2019-08-05 (2113)

Influence of short-term heat treatment on the microstructure and mechanical properties of EN AW 6060 T4 extrusion profiles - Part A - Fröck, H.; Graser, Matthias; Reich, M.; Lechner, Michael; Merklein, Marion; Keßler, O. (Production Engineering, 2016)
LFT Import::2019-08-07 (2180)

Influence of short-term heat treatment on the microstructure and mechanical properties of EN AW‑6060 T4 extrusion profiles – Part B - Graser, Matthias; Fröck, H.; Lechner, Michael; Reich, M.; Keßler, O.; Merklein, Marion (Production Engineering, 2016)
LFT Import::2019-07-29 (2179)

Influence of the Material Combination on the Load-bearing Capacity of Shear-clinched Joints - Wiesenmayer, Sebastian; Graser, Matthias; Merklein, Marion (1st International Conference on Advanced Joining Processes AJP 2019, 2019)

Influence of the properties of the joining partners on the load-bearing capacity of shear-clinched joints - Wiesenmayer, Sebastian; Graser, Matthias; Merklein, Marion (Journal of Materials Processing Technology, 2020)
Shear-clinching requires a minimum ductility for the punch-sided sheet material. A promising approach to overcome this limitation is a local short-term heat treatment of the upper joining partner in the joining zone. However, the design of heat treatment layouts for high-strength aluminum alloys necessitates fundamental knowledge on the mechanisms in shear-clinching processes in dependence of the properties of both joining partners. Therefore, within the paper, the mechanisms in shear-clinching were analyzed for a common aluminum magnesium alloy of the 5000 series, an alloy of the 6000 series with higher strength and a high-strength alloy of the 7000 series. On the die-side, hot stamped 22MnB5 and the dual phase steel HCT780X was utilized. For upper sheet materials with higher strength, the radial material extrusion of the upper joining partner decreases, which leads to the increase of the material volume in the joining zone and therefore to a larger bottom thickness and interlock. In addition, the decreased penetration of the outer punch results in a larger upper neck thickness. Due to the larger load-bearing cross section and the higher tensile strength, higher forces can be transmitted for high-strength materials. However, the low ductility of high-strength materials results in a failure of the joint at lower displacements and therefore in a decreased energy absorption. The found mechanisms provide the theoretical basis for the design of heat treatment layouts for high-strength aluminum alloys.
CRIS-Team Scopus Importer:2020-04-24
Keywords: Heat treatment; High-strength aluminum; High-strength steel; Joining; Multi-material design

Linked heat treatment and bending simulation of aluminium tailored heat treated profiles - Froeck, Hannes; Graser, Matthias; Reich, Michael; Lechner, Michael; Merklein, Marion; Kessler, Olaf (Minerals, Metals and Materials Series, 2017)
Precipitation hardening aluminium alloys enable tailoring of mechanical properties through the dissolution of strength-increasing precipitates during a local short-term heat treatment. Tailor Heat Treated Profiles (THTP) are aluminium extrusion profiles with locally different material properties, specifically optimised for succeeding bending processes. Softened areas need to be generated next to hardened areas to optimise the material flow during the forming process. To determine the optimised layout of softened and hardened areas, a process chain simulation consisting of the simulation of the short-term heat treatment and the subsequent forming process seems purposeful. The numerical modelling of short-term heat treatment requires a coupled computation of thermal and mechanical simulation with particular focus on the evaluation of microstructure and consequently on the change of mechanical properties. The dissolution and precipitation behaviour during heating and cooling of aluminium profiles 6060 T4 is investigated using differential scanning calorimetry. Thermo-mechanical analysis is applied for evaluation of the mechanical properties. This behaviour should be described in a material model with the software LS DYNA. The heat treatment simulation provides a distribution of mechanical properties along the profile, which is an important input parameter for the following forming simulation. In order to avoid a loss of information between the heat treatment simulation and forming simulation, both linked simulations are performed with the software LS DYNA.
CRIS-Team Scopus Importer:2023-03-29
Keywords: Aluminium alloy; Differential scanning calorimetry; EN AW-6060; Tailor heat treated profiles (THTP)

Numerical modelling approach for the temperature dependent forming behaviour of Ti-6Al-4V - Papke, Thomas; Graser, Matthias; Merklein, Marion (Proceedings of the 5th International Conference on New Forming Technology, MATEC Web of Conferences, 2018)
Titanium alloys offer several beneficial characteristics, such as high specific strength, metallurgical stability at elevated temperature, biocompatibility and corrosion resistance. With regard to these superior properties, Ti-6Al-4V is a commonly used titanium alloy for aerospace components and medical products. The production of parts made of Ti-6Al-4V can be done in various ways. One approach is forming at elevated temperature, which requires a focused design of parts, processes and numerical modelling of the forming process. Essential input parameters for the numerical models are temperature dependent material parameters. Since, the yield stress and Young's modulus of the material decrease significantly at elevated temperature, the forming limits are enhanced. For the characterization of the forming behaviour, uniaxial tensile tests at temperatures from 250 °C to 400 °C have been conducted. The samples are heated by conduction in a thermal-mechanical simulator for the tensile test. However, the resulting inhomogeneous temperature distribution along the longitudinal axis of the specimen is a challenge in order to measure proper material properties. Inhomogeneous temperature distribution leads to varying mechanical properties and temperature dependent forming behaviour. To overcome this issue, simple numerical models based on experimental data are necessary, which allow the estimation of the influence of the inhomogeneous temperature distribution. In this paper, therefore, the temperature distribution and the subsequent tensile test are investigated using electrical-thermal and mechanical numerical simulations of the tensile test at elevated temperature. With the combined approach of experimental tests and numerical simulations, the forming behaviour of Ti-6Al-4V can be modelled.
LFT Import::2019-08-05 (2305)
Keywords: Modelling; Thermal effects; Titanium

Numerical modelling of the process chain for aluminium Tailored Heat-Treated Profiles - Fröck, Hannes; Graser, Matthias; Reich, Michael; Lechner, Michael; Merklein, Marion; Kessler, Olaf (Advanced Modeling and Simulation in Engineering Sciences, 2023)
Lightweight construction in modern car design leads to an increased usage of various aluminium semi-finished products. Besides sheet material, aluminium extrusion profiles are frequently used due to their high stiffness and variety of possible cross-sections. However, similar to sheet material, aluminium profiles exhibit limited formability in comparison to mild steel materials. One possibility to increase the forming limits of precipitation hardened aluminium alloys is the so-called Tailored Heat Treatment technology. By a local short-term heat treatment, the material is softened and the material flow can be controlled to reduce stresses in critical forming zones. The purposeful definition of the heat treatment zones is mandatory to improve the forming results. Therefore, numerical methods are necessary. In this investigation, a numerical process chain is presented. It combines the thermo-mechanical simulation of a local laser heat treatment with a subsequent bending process of the heat-treated profile using the alloy EN AW-6082. The temperature distribution, mechanical properties, and finally, the bending result of the numerical model are validated by experimental tests.
CRIS-Team Scopus Importer:2023-06-30
Keywords: Aluminium alloy; Anisotropy; Bending simulation; EN AW-6082; LS-Dyna; Material model; Process chain simulation; Tailored Heat-Treated Profiles

On the inverse identification of Lankford coefficients using geometrical changes under quasi-biaxial loading - Graser, Matthias; Lenzen, Matthias; Merklein, Marion (International Journal of Material Forming, 2019)
Finite element simulation has become an important tool of process and production design in various fields, especially in the automotive industry. The calculation of forming processes in the early concept phase of new cars allows virtual adaptions, which can reduce costs of later phases in the product development significantly. Therefore, the precise characterization and modelling of the material behavior is necessary to ensure a robust and reliable numerical process design. The mechanical properties of numerous materials are highly influenced by the rolling or extrusion direction in the production process. This necessitates the characterization of materials in different loading directions. However, depending on the dimensional aspects of the semi-finished product, the manufacturing of specimens can be challenging or even impossible. Thus, in this investigation, an innovative, indirect approach for the identification of the Lankford coefficient in transversal direction is presented. Based on numerical and experimental data of layer compression tests the Lankford coefficient is determined by inverse modelling of the resulting specimen contour. Due to the characteristics of the layer compression test, it can even be used for semi-finished products with small transversal dimensions like extruded profiles. The presented methodology is on the one hand verified by conventional uniaxial tensile tests for aluminum as well as steel blank material. On the other hand it is used to determine Lankford coefficients for an aluminum extrusion hollow profile and the inversely identified material model is validated by comparison of strain distributions of experimental and numerical square tube bending tests.
CRIS-Team Scopus Importer:2019-08-06
Keywords: Inverse parameter identification; Lankford coefficient; Layer compression test; Material modelling

Precipitation behaviour and mechanical properties during short‑term heat treatment for tailor heat treated profiles (THTP) of aluminium alloy 6060 T4 - Fröck, Hannes; Graser, Matthias; Milkereit, Benjamin; Reich, Michael; Lechner, Michael; Merklein, Marion; Kessler, Olaf (Materials Science Forum, 2017)
Precipitation hardening aluminium alloys are widely used for automotive applications. To enhance the application of aluminium profiles, improved formability is needed. Tailor Heat Treated Profiles (THTP) with locally different material properties attempt to increase formability e.g. in bending processes. Tailoring of local properties is obtained by a local short-term heat treatment, dissolving the initial precipitate state (retrogression) and still allowing subsequent ageing. In the present study, the dissolution and precipitation behaviour of the aluminium alloy EN AW-6060 T4 was investigated during heating with differential scanning calorimetry (DSC). Heating curves from 20 to 600 °C with heating rates of 0.01 up to 5 K/s were recorded. Interrupted heat treatments with different maximum temperatures were performed in a deformation dilatometer. Immediately afterwards, tensile tests were carried out at room temperature. The course of the recorded mechanical properties as a function of the maximum temperature is discussed with regard to the dissolution and precipitation behaviour during heating. Finally, the aging behaviour of the investigated alloy was recorded after different typical short-term heat treatments and is discussed with reference to the DSC‑curves. The correlation of the microstructure and the mechanical properties enables the derivation of optimal parameters for the development of THTP through a local softening.
CRIS-Team Scopus Importer:2023-03-29
Keywords: Differential scanning calorimetry; Dissolution; EN AW-6060; Precipitation; Re-aging; Tailor heat treated profiles (THTP)

Tailoring material properties in forming technology by a local heat treatment - Merklein, Marion; Graser, Matthias; Degner, Julia; Lechner, Michael; Herrmann, Jürgen (Advanced Metal Forming Processes in Automotive Industry, 2016)
LFT Import::2019-08-05 (2177)

Verbesserung der Umformbarkeit von Aluminium - Graser, Matthias; Degner, Julia; Böhm, Wolfgang; Merklein, Marion (Konstruktion, 2017)
CRIS-Team Scopus Importer:2023-03-29